1986
DOI: 10.1159/000124242
|View full text |Cite
|
Sign up to set email alerts
|

Prolactin Cell Activity in Female and Male Syrian Hamsters: An Apparent Sexually Dimorphic Response to Light Deprivation and Pinealectomy

Abstract: In order to determine the role of the pineal gland in mediating the effects of long-term light deprivation on prolactin (PRL) cell activity in a highly photosensitive species, PRL synthesis, storage and release were determined in both female and male Syrian hamsters that were either blind, blind and pinealectomized or left intact for 14 weeks. PRL release was determined in vivo by measuring the amount of immunoreactive (RIA) PRL in the serum of the animals in each group with a heterologous RIA for hamster PRL.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
22
0

Year Published

1987
1987
2002
2002

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 15 publications
6
22
0
Order By: Relevance
“…Previous studies [32,33] have indicated that a depres sion in pituitary PRL content, mRNA levels, newly syn thesized PRL and pituitary RIA PRL accompany light deprivation in male hamsters. These studies were based on animals killed during the day (pituitaries [32] were removed between 08.00 and ll.OOh and incubated for 3 h) when, in our experiment, daytime assayable levels are also very low.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Previous studies [32,33] have indicated that a depres sion in pituitary PRL content, mRNA levels, newly syn thesized PRL and pituitary RIA PRL accompany light deprivation in male hamsters. These studies were based on animals killed during the day (pituitaries [32] were removed between 08.00 and ll.OOh and incubated for 3 h) when, in our experiment, daytime assayable levels are also very low.…”
Section: Discussionmentioning
confidence: 96%
“…These studies were based on animals killed during the day (pituitaries [32] were removed between 08.00 and ll.OOh and incubated for 3 h) when, in our experiment, daytime assayable levels are also very low. However, our study shows that a significant surge in pituitary PRL stores to control levels occurred during the night.…”
Section: Discussionmentioning
confidence: 99%
“…In hamsters, Blask et al [18]found that the suppressive effects of light deprivation and blindness for 14 weeks on PRL cell function seem to be pineal-dependent in males, while these effects would be partially pineal-independent in females. Thus, a dimorphism according to sex was especially evident, since in females a direct retinohypothalamic-suprachiasmatic input in structures of the medial basal tuberal region of the hypothalamus would regulate the function of the lactotropes, without the intervention of the pineal gland.…”
Section: Discussionmentioning
confidence: 99%
“…This may lead to atrophy of the reproductive organs by means of an induction in pineal activity, while pinealectomy (Px) prevents the suppressing effects on the lactotrope cells [1, 16, 17, 18]. This was especially effective in female hamsters, showing a dimorphism in accord with sex [19].…”
Section: Introductionmentioning
confidence: 99%
“…However, not all seasonal fluctuations in circulating PRL levels are solely dependent on the pineal melatonin signal. For example, it has been demonstrated that some of the inhibitory effects of a short-day photoperiod on PRL synthesis and release are still evident in pinealectomized female Syrian hamsters [6]. In addition, hypothalamic knife cuts in the paraventricular nucleus (PVN) region that abolish the rhythm in pineal melatonin activity result in declines in circulating PRL regardless of ambient photoperiod [7].…”
Section: Introductionmentioning
confidence: 99%